Pengaruh Pengendalian Internal, Budaya Etis, Komitmen Afektif terhadap Kecenderungan Fraud dengan Kecerdasan Emosional sebagai Variabel Moderasi - Djanoearko, Rahma Ellok Satiti; Astuti, Christina Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to look for empirical evidence regarding whether there is an influence of internal control, ethical culture, and affective commitment on fraud tendencies, with emotional intelligence as a moderating variable. This research uses a quantitative method with primary data collected through a questionnaire as a form distributed to employees who work at the company with a related to asset management jobs. A total of 164 respondents were collected in this study who met the respondent criteria. Data processing was carried out using SmartPLS 3.0 software. The research results show that there is a significant negative influence between internal control, ethical culture, and affective commitment on fraud tendencies. Emotional intelligence strengthened the influence of affective commitment on fraud tendencies, but weakened the influence of internal control and ethical culture on fraud tendencies.